Frugal innovation in the age of digital transformation: a case study of a public Brazilian telemedicine system considering local socioeconomic context - Iasbech, Paulo Alberto Battazza (2021)
This study investigates “How frugal innovation (FI) and digital transformation impacts a public healthcare system considering the local socioeconomic context.”, contributing for the advances of Frugal Innovation theory in two ways: (i) first by introducing the local socioeconomic context as a fourth criteria to Weyrauch & Herstatt (2016) framework of to define frugal innovations, which adds much value to the existing framework and (ii) second by introducing sociomaterial bricolage lenses as an alternative to promote deeper understanding of socio interactions and cocreated practices of active agents and the constitutive entanglement involved, especially when dealing with Frugal Digital Innovation. We initiated by conducting a robust bibliometric review on Scopus database to deeply understand the state of the art on Frugal Innovation literature, starting with 157 articles and resulting to the 27 most important papers. Afterwards, we navigate by Digital Transformation literature, comprehending Cunha et al (2016) concept of levers of Digital Change, Western et al (2014) analysis of digital transformation elements and Beresford and Coelho (2018) idea of third wave. Connecting those ideas, we felt inspired by Ahuja and Chan (2016) discussion of Frugal IT Innovation, also latter on called Frugal Digital Innovation. We conducted an in-depth single case study (Stake,2005) on Telemedicine System of Santa Catarina (TSSC), a Brazilian public healthcare system that combines digital artifact and workflows, resulting on a frugal solution to support cost reduction while increasing healthcare access to population of Santa Catarina (Wallauer et al, 2008). As a result, we were able to provide evidences of how frugal innovation and digital transformation impacts a public healthcare system considering the local socioeconomic context, demonstrating the importance of the ‘Adherence to local socioeconomic context’ as a defining criteria of FI, but also identifying the lack of researches on FI applying practice-based theories and the benefits Sociomaterial Bricolage framework can provide for deeper understanding of social interactions inherent to FI solutions. It indicates that FI may begin a practice turn as other research fields have already experienced, such as Strategy and Information Systems.